Diversification of sterol methyltransferase enzymes in plants and a role for β‐sitosterol in oriented cell plate formation and polarized growth. (3rd November 2015) - Nakamoto, Masatoshi; Schmit, Anne‐Catherine; Heintz, Dimitri; Schaller, Hubert; Ohta, Daisaku
Summary: Phytosterols are classified into C24‐ethylsterols and C24‐methylsterols according to the different C24‐alkylation levels conferred by two types of sterol methyltransferases (SMTs). The first type of SMT (SMT1) is widely conserved, whereas the second type (SMT2) has diverged in charophytes and land plants. The Arabidopsis smt2 smt3 mutant is defective in the SMT2 step, leading to deficiency in C24‐ethylsterols while the C24‐methylsterol pathway is unchanged. smt2 smt3 plants exhibit severe dwarfism and abnormal development throughout their life cycle, with irregular cell division followed by collapsed cell files. Preprophase bands are occasionally formed in perpendicular directions in adjacent cells, and abnormal phragmoplasts with mislocalized KNOLLE syntaxin and tubulin are observed. Defects in auxin‐dependent processes are exemplified by mislocalizations of the PIN2 auxin efflux carrier due to disrupted cell division and failure to distribute PIN2 asymmetrically after cytokinesis. Although endocytosis of PIN2–GFP from the plasma membrane (PM) is apparently unaffected in smt2 smt3, strong inhibition of the endocytic recycling is associated with a remarkable reduction in the level of PIN2–GFP on the PM. Aberrant localization of the cytoplasmic linker associated protein (CLASP) and microtubules is implicated in the disrupted endocytic recycling in smt2 smt3 . Exogenous C24‐ethylsterols partially recover lateral root development and auxin distribution in smt2 smt3 roots. These results indicate that C24‐ethylsterols play a crucial role in division plane determination, directional auxin transport, and polar growth. It is proposed that the divergence of SMT2 genes together with the ability to produce C24‐ethylsterols were critical events to achieve polarized growth in the plant lineage. Significance Statement: Sterol methyltransferases (SMTs) mediate formation of C24‐ethylsterols and C24‐methylsterols. Here we use a double mutant, smt2 ; smt3, which is deficient in C24‐ethylsterols to show that C24‐ethylsterols are important for cell division and for auxin transport. We suggest that the divergence of gene function to yield C24‐ethylsterols might have contributed to the evolution of polarized plant growth.